THE EFFECT OF E-SERVICE QUALITY, CUSTOMER EXPERIENCE, AND EXPERIENTAL MARKETING ON GRABFOOD USER SATISFACTION OF UNPRI STUDENTS IN MEDAN CITY - Nicolas; Christian Adianta Ginting; Lenny Fransiska; Januardin (Mount Hope Economic Global Journal, 2025)
Grab Food in facing tight competition must strive to maintain its position not to be shifted by Go-Food. The purpose of this study is to test the Influence of E-Service Quality, Customer Experience and Experiential Marketing on Grab Food User Satisfaction on Unpri Students in Medan City. This research method is descriptive. Quantitative research approach. The population is Unpri Students in Medan City, the number is unknown. The sample is 73 Unpri Students in Medan City. The model is with multiple linear regression. The result is E-Service Quality has an impact on Grab Food User Satisfaction on Unpri Students in Medan City. Customer Experience has an impact on Grab Food User Satisfaction on Unpri Students in Medan City. Experiential Marketing has an impact on Grab Food User Satisfaction on Unpri Students in Medan City. E-Service Quality, Customer Experience and Experiential Marketing have an impact on Grab Food User Satisfaction on Unpri Students in Medan City.